Management of extensive nerve gaps of more than 5 cm by vein graft in three cases - Singh, Sudhir (International Surgery Journal, 2020)
The aim of this study was to evaluate the effectiveness of use of extensive vein grafts to manage nerve gap repair. The study on peripheral nerve injury has been carried out in this country as well as abroad for many years, but the use of veins as the conduit is more than three decades old and still in evolving phase for standard clinical procedure. Its application is simple and regeneration of nerve is quite satisfactory specially for nerve gap of less than 5 cm. However, the present study was done on extensive nerve gaps of more than 5 cm to 10 cm gaps specially of after long duration of injury to see the results. Inspite of poor results due to extensive nerve gap and treatment tried after long duration of injury, it is quite encouraging to see nerve growth in biopsy of one venous tube and it is great achievement for future study. As of now any vein tube applied for nerve gap of more than five cm is not successful. So successful use of venous tubes is still in infancy for nerve gap of more than 5 cm.